Northern political culture?: Political behaviour in Nunavut - Henderson, Ailsa (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2004)
AbstractThe realities of political life in Nunavut suggest that levels of political engagement would be lower than that found in southern Canada. The absence of political parties affects both the method of political campaigning and the operation of the legislature while the existence of Inuit birthright organizations provide a parallel system of governance and several more opportunities to vote and to stand for election. Levels of turnout are lower than average for federal elections and lower still for the birthright organizations. For territorial elections, however, turnout levels are much higher. An analysis of predictors of voting demonstrates that age, income and education have a positive impact on turnout. Inuit, and those with positive evaluations of the land claim and Nunavut, are also more likely to vote. In its investigation of political office, the paper also demonstrates that there are elected positions for 1% of the population in Nunavut, compared with .0075% in a typical Canadian community. The paper is the first to examine political behaviour in the North from a quantitative perspective and carefully points out methodological issues affecting the treatment of data. It ends by arguing that southern models of political behaviour should be treated with caution in Nunavut.